Multi-omics profiling reveals elevated CO2-enhanced tolerance of Trifolium repens L. to lead stress through environment-plant-microbiome interactions - Lei Wang; Sui Wang; Haifeng Su; Hongguang Cai; Yankun Song; Xiang Gong; Zhihui Sun; Jianhua Qu; Ying Zhang (Environment International)
The increasing atmospheric CO2 resulting from human activities over the past two centuries, which is projected to persist, has significant implications for plant physiology. However, our predictive understanding of how elevated CO2 (eCO2) modifies plant tolerance to metal stress remains limited. In this study, we collected roots and rhizosphere soils from Trifolium repens L. subjected to lead (Pb) stress under ambient and elevated CO2 conditions, generating transcriptomic data for roots, microbiota data for rhizospheres, and conducting comprehensive multi-omics analyses. Our findings show that eCO2 reduced the accumulation of Pb-induced reactive oxygen species (ROS) and promoted plant growth by 72% to 402%, as well as increases shoot Pb uptake by 79% compared to ambient CO2. Additionally, eCO2 triggers specific defense response in T. repens, elevating the threshold for stress response. We observed a adaptive reconfiguration of transcriptional network that enhances energy efficiency and optimizes photosynthetic product utilization. Notably, eCO2 induces salicylic acid biosynthesis and activates defense pathways related to redox balance and ROS scavenging processes, thereby enhancing abiotic stress resistance. Through weighted gene co-expression network analysis, our comprehensive investigation reveals a holistic regulatory network encompassing plant traits, gene expression patterns, and bacterial structure potentially linked to metal accumulation as well as tradeoffs between growth and defense in plants under elevated CO2. These insights shed light on the plant stress responses under elevated CO2 and while contributing to a broader comprehension of plant-environment interactions.